Creating engaging discussions : strategies for "avoiding crickets" in any size classroom and online - Nilson, Linda Burzotta (Stylus Publishing, LLC, 2018)
Jennifer H. Herman and Linda B. Nilson demonstrate how to create the conditions to facilitate deep and meaningful learning as well as to assess the effectiveness of discussions. They identify, analyze, and solve common problems in both classroom and online discussions and in both small and large classes. They take a direct, practice-oriented approach that--in acknowledging common challenges--provides principles, guidance on design, examples of activities and techniques, and eight detailed case studies. These cases demonstrate successful approaches that faculty across disciplines and from a variety of institutions have adopted in their face-to-face, blended, or online courses at the undergraduate or graduate level. The case authors begin by describing the original pedagogical challenge they faced and explain how they addressed it and assessed the results of their innovation. They also offer practical recommendations to readers who may want to try their strategies.